1983
DOI: 10.3109/00365528309182088
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Ulcerative Colitis

Abstract: The course of pregnancy in 97 women with ulcerative colitis was studied over a 12-year period. During this period they had 173 pregnancies and delivered 136 children. There were two gemellary deliveries. Nine women had a spontaneous and 16 an induced abortion, of which 4 were performed on therapeutic indication. For a woman with ulcerative colitis the risk of an exacerbation of the bowel disease was 32% per year in her fertile years, whereas it was 34% per year during pregnancy. This difference is not statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
2
18

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(160 citation statements)
references
References 15 publications
9
131
2
18
Order By: Relevance
“…Large population-based studies conducted in the 1970s in Europe by Nielsen et al established that in both UC and CD patients, rates of disease flare are similar between pregnant and nonpregnant women [9]. Specifically, Nielsen reported UC flare rates of 34 versus 32% in pregnant and nonpregnant women, respectively.…”
Section: Effect Of Pregnancy On Disease Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Large population-based studies conducted in the 1970s in Europe by Nielsen et al established that in both UC and CD patients, rates of disease flare are similar between pregnant and nonpregnant women [9]. Specifically, Nielsen reported UC flare rates of 34 versus 32% in pregnant and nonpregnant women, respectively.…”
Section: Effect Of Pregnancy On Disease Activitymentioning
confidence: 99%
“…Earlier studies showed active disease at conception was associated with a higher rate of fetal loss [52] and preterm birth [9,28]. Disease activity during pregnancy has also previously been associated with preterm birth and low birthweight [37,46,53,54].…”
Section: Effect Of Ibd On Pregnancy Course and Pregnancy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications associated with IBD activity at the time of conception include: Abortion, low birth weight (LBW), and premature births [50,[52][53][54][55] . These complications again, are usually seen more often in CD patients than UC patients.…”
Section: Pregnancymentioning
confidence: 99%
“…Potential adverse effects of disease activity on fertility, potential pregnancy complications due to UC, potential adverse effects of the pregnancy itself on the course of UC, and the teratogenic potential of medications used in UC are troublesome issues for both patients with UC and physicians. Several studies have investigated the effects of UC on fertility and pregnancy and obtained contradictory results (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%